Measurement of focused ultrasonic fields based on colour edge detection and curve fitting. (23rd March 2016) - Zhu, H.; Chang, S.; Yang, P.; He, L.
Abstract: This paper utilizes firstly both a scanning device and an optic fiber hydrophone to establish a measurement system, and then proposes the parameter measurement of the focused transducer based on edge detection of the visualized acoustic data and curve fitting. The measurement system consists of a water tank with wedge absorber, stepper motors driver, system controller, a focused transducer, an optic fiber hydrophone and data processing software. On the basis of the visualized processing for the original scanned data, the −3 dB beam width of the focused transducer is calculated using the edge detection of the acoustic visualized image and circle fitting method by minimizing algebraic distance. Experiments on the visualized ultrasound data are implemented to verify the feasibility of the proposed method. The data obtained from the scanning device are utilized to reconstruct acoustic fields, and it is found that the −3 dB beam width of the focused transducer can be predicted accurately.